2018
DOI: 10.3390/tropicalmed3010024
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in Mexico, Central America, and the Caribbean

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, an endemic disease in tropical areas around the world. Cumulative human cases have demonstrated that melioidosis is prevalent and increasingly recognized in the American continent. Even though the first reports of melioidosis in Mexico, Central America, and the Caribbean Islands date back to the late 1940s, the potential of the disease as a public health concern in the region has not been fully appreciated. Unfortunately, recent studies predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…M elioidosis, caused by the telluric gram-negative rod Burkholderia pseudomallei, is endemic in Southeast Asia and northern Australia (1) but may be underdiagnosed in other tropical regions (2). Increasing occurrences have been reported in the Caribbean during the past few decades among persons with no exposure to known endemic areas (3)(4)(5). Tropical environmental conditions and the presence of this bacterium in soil samples in the Caribbean support the plausibility of endemicity (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…M elioidosis, caused by the telluric gram-negative rod Burkholderia pseudomallei, is endemic in Southeast Asia and northern Australia (1) but may be underdiagnosed in other tropical regions (2). Increasing occurrences have been reported in the Caribbean during the past few decades among persons with no exposure to known endemic areas (3)(4)(5). Tropical environmental conditions and the presence of this bacterium in soil samples in the Caribbean support the plausibility of endemicity (3).…”
mentioning
confidence: 99%
“…(3). The skin test became commercially available again in 2014 after more than a decade; it is approved for adults 18-64 of age who have a history of pulmonary coccidioidomycosis (3,4). However, little is known about its use…”
mentioning
confidence: 99%
“…20 From the published literature alone, a review recently reported 63 cases of melioidosis from Mexico, central America, and the Caribbean, establishing its endemicity within the region. 21 An excellent example of uncovering the hidden burden using increased surveillance, awareness, and WHO's laboratory capacity building program is that from Sri Lanka. 22 The first case was isolated in 1927 23 and up until 2000, a handful of isolated cases had been reported from Sri Lanka and on occasion even considered nonendemic for melioidosis.…”
Section: Global Burdenmentioning
confidence: 99%
“…Diabetes mellitus is a major risk factor, and individuals suffering from this disease are at higher risk for developing melioidosis than the rest of the population [3]. Bps is primarily found in tropical areas, mainly in northern Australia and the south of Asia, but it is being found more frequently in other tropical countries as well [4]. In Mexico, there have been 15 documented cases of melioidosis, between 1958 and 2018 [4], with the most recent resulting in the fatality of 2 teenaged siblings (aged 12 and 16) [5].…”
mentioning
confidence: 99%